The Implications of Decentralization for Integrated Coastal Management Sustainability in the Philippines - Sievanen, Leila (Silliman Journal, 2022)
In the 1991, the Philippines passed the Local Government Code (LGC) which itransferred many coastal management responsibilities from the Central Golicrurnent to Local Government Units (LGUs). Based on a decentralization framework proposed by Cohen (1999), this paper compares two case study sites to determine the effects of two forms of decentralization on coastal management outcomes and resulting sustainability implications. Mabini-ringloy, a popular tourist destination, is used to represent a case of "institutional pluralism" while Bais Bay is used to illustrate a case of a "distributed institutional monopoly." While decentralized approaches are often critiqued for limited resources, failure to encourage commitment of local officials, lack of coordination between groups, and low local-level technical and managerial capacity, this paper argues that a situation of institutional pluralism has the potential to better allow non-central and private sector institutions and firms to carry out task-related roles more accountably, effectively, and efficiently than governmental institutions holding monopolies over public sector tasks. In the Philippines, these institutions must have a good relationship with the LGU since LGUs have a great deal of political power in the current framework. Tasks will be carried out more accountably, effectively, and efficiently in situations with an accountable private sector, political space necessary to accomplish public sector tasks, and an expressed agenda to accomplish these tasks.